Analisis ekonoml terhadap Hukum sebagai Upaya Peningkatan PerananHukum dalamPembangunan - hanafi amrani (Jurnal Hukum IUS QUIA IUSTUM, 2001)
There thre models of theory application into law studies, namely positive or predictive economics, descriptive economics and normative or prescriptive economics on the other hand, the economical theories which can explain about law institutions are price theory maximalisation theory, equilibrium theory, efficiency theory andso on-All of these theories couldprovide add values In law research.